2022
DOI: 10.24018/ejdent.2022.3.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Analytical Study to Determine Knowledge and Attitude of Dental Students about COVID-19 Disease and Its Precautionary Measures

Abstract: Objective: To determine knowledge and attitude of dental and medical students about COVID – 19 disease and its precautionary measures Methodology: The study was conducted after approval from the ethical review committee of the Foundation University College of Dentistry, Islamabad from June 2021 to September 2021. Inclusion criteria adhered to the recruitment of fourth and final-year students of dentistry. Informed written consent was taken after explaining the study protocol. The format of the questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…61 62 A similar association had stated in another study by Abbas et al from Pakistan. 11 In addition to dental caries, periodontal health is also interconnected with other oral health problems including malocclusion reported in other studies. 63 64 This dependency on periodontal health would be grounded on the foundation of the type and severity of the malocclusion.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…61 62 A similar association had stated in another study by Abbas et al from Pakistan. 11 In addition to dental caries, periodontal health is also interconnected with other oral health problems including malocclusion reported in other studies. 63 64 This dependency on periodontal health would be grounded on the foundation of the type and severity of the malocclusion.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, few schools-based studies have reported a prevalence of malocclusion ranging from 73.2 to 75.6%. 11 42 The probable high prevalence of malocclusion might be due to different study parameters and targeting specific population groups, rather than targeting the general population by Abbas et al 11 Similarly, the study conducted by Nazir et al 43 targeted the vulnerable population. The possibility of limited resources and lack of good oral hygiene maintenance for a longer duration at an early age could inflate the prevalence of malocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations